2022
DOI: 10.4269/ajtmh.21-0685
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Epidemiology of Crimean-Congo Hemorrhagic Fever in Humans in Uganda, 2013–2019

Abstract: Crimean-Congo Hemorrhagic Fever (CCHF) is endemic in Uganda, yet its epidemiology remains largely uncharacterized. To better understand its occurrence within Uganda, case reports of patients hospitalized with CCHF between 2013 and 2019 were reviewed. Further, genome sequences of CCHF-positive RNA obtained during this period were determined for phylogenetic comparisons. We found that a total of 32 cases (75% males; CFR, 31.2%), aged between 9 to 68 years, were reported during the study period. Most cases were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…In Uganda, previous reports have indicated that over 65% of human cases in the country occur among animal handlers [ 25 ]. Evidence of CCHFV prevalence in humans and ticks has been documented in this and other studies [ 26 28 ]; however, serosurvey of CCHF in livestock either as part of a viral haemorrhagic fever surveillance program or during outbreaks has not been well described.…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, previous reports have indicated that over 65% of human cases in the country occur among animal handlers [ 25 ]. Evidence of CCHFV prevalence in humans and ticks has been documented in this and other studies [ 26 28 ]; however, serosurvey of CCHF in livestock either as part of a viral haemorrhagic fever surveillance program or during outbreaks has not been well described.…”
Section: Discussionmentioning
confidence: 99%
“…R. appendiculatus ticks, the most prevalent species, are known to be widespread in Uganda and lack seasonal variation in abundance (17)(18)(19)(20). They are also well-described vectors for zoonotic diseases, as they feed on a wide range of animals as well as humans (21,22), including CCHFV (23,24), Nairobi Sheep Disease Virus (NSDV) (25) and Kadam virus (26,27), all of which are prevalent in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…We selected two areas within the cattle corridor (Nakaseke and Lyantonde), classified as high risk districts because of their location in an area of high cattle density and previously-reported human cases of CCHF in the area (Fig 1). We also selected an area (Arua district) outside the cattle corridor (24,29,37,38), classified as a low-risk area where CCHF had never previously been reported, as a control site. The study in Lyantonde coincided with a CCHF outbreak, and ecological sampling of ticks for virome analysis was undertaken as part of an outbreak investigation (39).…”
Section: Methodsmentioning
confidence: 99%
“…We have developed a VSV-based SUDV-specific vaccine candidate expressing the SUDV-Gulu strain GP instead of the VSV glycoprotein (G) (here designated VSV-SUDV). SUDV-Gulu is the causative strain of the biggest recorded SVD outbreak from 2000/01 in Uganda (Table S1) and phylogenetically closer than the original SUDV-Boniface strain to the current outbreak strain 13 . The vaccine vector is based on the VSV G replacement approach and, thus, in principle identical to VSV-EBOV.…”
Section: Introductionmentioning
confidence: 89%